The Impact of Inequality of Opportunity on Income Disparity: A Case of Pakistan - Ur Rehman, Naeem; Hashmat, Afsheen; Kanwal, Rimsha (Minhaj International Journal of Economics and Organization Sciences, 2022)
This study is deliberated to explore the effect of Role of inequality of opportunity in the determination of income disparity in Pakistan. The data set from 1990 to 2020 has been taken for this study from World Bank. To check the short run and long run relationship among inequalities of opportunity in the determination of income disparity employed Autoregressive Distributed Lag (ARDL) bound testing used. The ARDL co-integration results indicate that there is a negative relationship of health and education inequality on income inequality in short run, while all other variables like gross domestic product (GDP) foreign direct investment (FDI) and domestic investment (DI) are also negatively linked with income inequality. In long run, only education inequality, health inequality and domestic investment (DI) are negatively related with income inequality. And all other variables gross domestic product (GDP) and foreign direct investment (FDI) are positively connected with income inequality. Government should implement a progressive tax system where higher-income individuals and corporations are taxed at a higher rate. Investing in education and skills training programs enables individuals from disadvantaged backgrounds to acquire the knowledge and skills necessary for higher-paying jobs. Governments can enhance access to quality education, vocational training, and scholarships to promote social mobility and reduce income inequality. Overall, the study highlights the importance of addressing inequality of opportunity in order to reduce income disparity in Pakistan. By implementing targeted policies and investing in education and skills development, governments can work towards creating a more equitable society with reduced income inequality.